Ieinteresētās personas un riska pārvaldība par projekta panākumiem - Dubey, Vipin (Latvijas Universitāte, 2025)
This research Project analyzes risk mitigation measures and the effectiveness of those strategies in minimizing cost overruns in megaprojects involving infrastructure design and construction. The purpose of this study is to determine the fundamental factors that contribute to budget overruns and to provide a comprehensive framework for risk management over the whole lifetime of the project. The study uses descriptive and inferential statistical techniques, such as analysis of variance (ANOVA), t-tests, and regression analysis, to validate key risk factors and mitigation strategies. The study draws on both primary data, which consists of survey questionnaires filled out by 350 industry professionals, and secondary sources, which include scholarly journals, reports from the government and banks, and whitepapers. The research is innovative because it takes a holistic approach, which combines disparate risk information into a cohesive model that incorporates technology, stakeholder coordination, regulatory alignment, and adaptive governance. This approach is what makes the research so original. These findings have theoretical significance because they add real-time and sociopolitical components to risk and cost control models, which enriches these models. From a practical standpoint, the research provides ideas for policy and management that may be implemented to improve the accuracy of budgeting, the participation of stakeholders, and the efficiency with which projects are carried out. In spite of some constraints, such as a cross-sectional design and a sector-specific emphasis, the study makes significant contributions to both the academic world and the professional world. It does this by addressing ongoing issues in the execution of infrastructure projects and by improving strategic cost control.

Infrastructure Mega-Projects, Cost Overruns, Risk Mitigation, Project Management, Integrated Risk Framework, Budget Control, Adaptive Governance. Stakeholder Coordination
Stakeholder and Risk Management on Project Success
Keywords: Ekonomika un uzņēmējdarbība; Infrastructure Mega-Projects; Cost Overruns; Risk Mitigation; Project Management; Integrated Risk Framework